Aberrant left brachiocephalic vein is a contraindication for anterior cervicothoracic approach - Ong, Edwin Kean Siong; Wong, Tat Seng; Chung, Weng Hong; Chiu, Chee Kidd; Saw, Aik; Hasan, Mohd Shahnaz; Chan, Chris Yin Wei; Kwan, Mun Keong (SAGE Publications (UK and US), 2019)
Aberrant left brachiocephalic vein is a rare condition. Its occurrence in patients requiring anterior cervicothoracic approach for severe kyphoscoliosis has not been described. A 16-year-old male with neurofibromatosis and severe upper thoracic kyphoscoliosis presented to us with curve progression. Halo gravity traction was attempted but failed to achieve significant correction. Subsequently, he underwent halo-pelvic traction and later Posterior Spinal Fusion (PSF) from C2 to T10. Second-stage anterior cervicothoracic approach with anterior fibula strut grafting was planned; however, preoperative computed tomography angiography revealed an aberrant left brachiocephalic vein with an anomalous retrotracheal and retroesophageal course, directly anterior to the T5/T6 vertebrae (planned anchor site for fibula strut graft) before draining into superior vena cava. Therefore, surgery was abandoned due to the risks associated with this anomaly. Aberrant left brachiocephalic vein is rare, the presence of which could be a contraindication for anterior cervicothoracic approach. Assessment of the anterior neurovascular structures is crucial in preoperative planning. © The Author(s) 2019.